2017
DOI: 10.1021/acs.biomac.7b00823
|View full text |Cite
|
Sign up to set email alerts
|

Drying Affects the Fiber Network in Low Molecular Weight Hydrogels

Abstract: Low molecular weight gels are formed by the self-assembly of a suitable small molecule gelator into a three-dimensional network of fibrous structures. The gel properties are determined by the fiber structures, the number and type of cross-links and the distribution of the fibers and cross-links in space. Probing these structures and cross-links is difficult. Many reports rely on microscopy of dried gels (xerogels), where the solvent is removed prior to imaging. The assumption is made that this has little effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 56 publications
7
109
0
Order By: Relevance
“…It has also recently been shown that SANS can be used to follow the drying process if suitable contrast is achieved using deuterated dipeptide-based gelators. 24 The data showed that the scattering primarily probed the primary fibres, not aggregated fibres that were imaged using SEM.…”
Section: Small Angle Scatteringmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also recently been shown that SANS can be used to follow the drying process if suitable contrast is achieved using deuterated dipeptide-based gelators. 24 The data showed that the scattering primarily probed the primary fibres, not aggregated fibres that were imaged using SEM.…”
Section: Small Angle Scatteringmentioning
confidence: 98%
“…For example, we have shown that drying a dipeptide-based LMWG leads to the fibres becoming much thicker than the primary structures which are observed using cryo-TEM. 24 Further issues can arise from the use of a stain for TEM, which can potentially lead to structural changes. It should also be stated that both SEM and TEM have such high magnifications that only a tiny fraction of a sample can be imaged in a realistic timeframe, meaning that there is always the question as to whether the images are representative.…”
Section: Microscopymentioning
confidence: 99%
“…Although microscopic techniques are powerful, there is a requirement for drying and/or freezing during the sample preparation, which may cause artifacts that change the self-assembled structure. [11] Furthermore, these techniques cannot discriminate chemical species in multicomponent systems. Recently, confocal laser scanning microscopy (CLSM) has emerged as a powerful tool for structural analysis of multicomponent supramolecular hydrogel systems ( Figure 1).…”
Section: Stimulus-responsive Supramolecular Hydrogelsmentioning
confidence: 99%
“…However, Mears et al. previously reported that due to the drying process required for sample preparation, SEM does not always show the primary network of fibers but instead depicts the aggregation of the fibers . The size of the fibers in the SEM images is therefore probably not representative of the size of the fibers in the gel state.…”
Section: Figurementioning
confidence: 97%
“…However,M ears et al previously reported that due to the drying process required for sample preparation,S EM does not always show the primary network of fibers but insteadd epicts the ag- www.chemeurj.org gregation of the fibers. [18] The size of the fibers in the SEM images is therefore probably not representative of the size of the fibers in the gel state. It can also be observed that fibers of gel 8 appear to be aligned parallelt oe ach other whereas fibers in gel 9 arranged aroundc enters in star-like patterns.…”
mentioning
confidence: 99%